2011
DOI: 10.1073/pnas.1100584108
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide profiling of diel and circadian gene expression in the malaria vector Anopheles gambiae

Abstract: Anopheles gambiae, the primary African vector of malaria parasites, exhibits numerous rhythmic behaviors including flight activity, swarming, mating, host seeking, egg laying, and sugar feeding. However, little work has been performed to elucidate the molecular basis for these daily rhythms. To study how gene expression is regulated globally by diel and circadian mechanisms, we have undertaken a DNA microarray analysis of An. gambiae under light/ dark cycle (LD) and constant dark (DD) conditions. Adult mated, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
274
2
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(286 citation statements)
references
References 118 publications
9
274
2
1
Order By: Relevance
“…We have shown here that, in A. aegypti female mosquitoes, expression of JH-dependent Kr-h1 and Hairy genes requires light/dark daily rhythms and oscillated, gradually rising to the maximal level by the fourth day of PE development. Genomewide profiling of PE females of the mosquito Anopheles gambiae has demonstrated that at least 16% of genes with various biological functions are under light/dark rhythm control (24). However, whether JH III is involved in this in Aedes mosquitoes has not been identified.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown here that, in A. aegypti female mosquitoes, expression of JH-dependent Kr-h1 and Hairy genes requires light/dark daily rhythms and oscillated, gradually rising to the maximal level by the fourth day of PE development. Genomewide profiling of PE females of the mosquito Anopheles gambiae has demonstrated that at least 16% of genes with various biological functions are under light/dark rhythm control (24). However, whether JH III is involved in this in Aedes mosquitoes has not been identified.…”
Section: Discussionmentioning
confidence: 99%
“…To identify CCGs and understand the mechanism of their regulation, microarrays have been used to profile rhythmic gene expression systematically in cyanobacteria, plants, insects, fungi, mice, and cellular models (Atwood et al, 2011;Covington, Maloof, Straume, Kay, & Harmer, 2008;Hughes et al, 2009;Hughes, Hong, et al, 2012;Keegan, Pradhan, Wang, & Allada, 2007;Kornmann, Schaad, Bujard, Takahashi, & Schibler, 2007;McGlincy et al, 2012;Menger et al, 2007;Rund, Hou, Ward, Collins, & Duffield, 2011;Vollmers et al, 2009;Xu, DiAngelo, Hughes, Hogenesch, & Sehgal, 2011). These studies have contributed significantly to our understanding of circadian output in wild-type animals, and over time they have matured into investigations of more focused tissues and cell types (Collins, Kane, Reeves, Akabas, & Blau, 2012;Kula-Eversole et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The brightness changing unleash the gene expression that control the mosquitoes activities (Ptitsyn et al, 2011;Rund et al, 2011).…”
Section: Introductionmentioning
confidence: 99%